2015
DOI: 10.1159/000437429
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neuroprotective Effects of Combination Therapy with Bone Marrow-Derived Mesenchymal Stem Cells and <b><i>Ginkgo biloba</i></b> Extract (EGb761) in a Rat Model of Experimental Autoimmune Encephalomyelitis

Abstract: Objectives: We investigated whether Ginkgo biloba extract (EGb761) can provide neuroprotective effects and enhance the efficacy of bone marrow-derived mesenchymal stem cells (BMSCs) in a rat model of experimental autoimmune encephalomyelitis (EAE). Methods: We examined the synergistic action of BMSCs combined with EGb761 treatment in EAE rats. The immunized rats received an intravenous injection of BMSCs or intraperitoneal administration of EGb761 or both on the day of the onset of clinical symptoms and for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Combination therapy of EGb 761 with bone-marrow-derived mesenchymal stem cells (BMSCs) has shown a synergistic effect in animals with autoimmune encephalomyelitis. The therapeutic mechanism involves the inhibition of pro-inflammatory cytokines, demyelination, and protection axons and neurons [ 142 ]. Other studies have documented that GA prevents p-Tau deposition and thus protects cells from toxicity associated with Tau hyperphosphorylation.…”
Section: Ginkgo Biloba Extract (Egb) For Neuroprotection and Potentia...mentioning
confidence: 99%
“…Combination therapy of EGb 761 with bone-marrow-derived mesenchymal stem cells (BMSCs) has shown a synergistic effect in animals with autoimmune encephalomyelitis. The therapeutic mechanism involves the inhibition of pro-inflammatory cytokines, demyelination, and protection axons and neurons [ 142 ]. Other studies have documented that GA prevents p-Tau deposition and thus protects cells from toxicity associated with Tau hyperphosphorylation.…”
Section: Ginkgo Biloba Extract (Egb) For Neuroprotection and Potentia...mentioning
confidence: 99%
“…This study also noted the activity of SOD and myeloperoxidase (MPO) ( Yang et al, 2013 ). Hao et al (2016) demonstrated the neuroprotective effect of EGb 761 when co-administered with bone marrow derived mesenchymal stem cells (BMSCs) in encephalomyelitis (EAE). Consequently, combination therapy with BMSCs and EGb 761 showed an synergistic effect in animals with experimental autoimmune encephalomyelitis through inhibition of pro-inflammatory cytokines, demyelination and protection of axons and neurons.…”
Section: The Use Of G Biloba In the Treatment And Prevention Of Admentioning
confidence: 99%
“…Song et al revealed the protective effects of Ginkgo biloba extract Ginkgolide B against acute SCI in rats, which may be related to the JAK/STAT signaling pathway [13]. Current reports have focused on the effects of Ginkgo biloba extracts on neuronal apoptosis and their neuroprotective effects after SCI [14,15]. However, whether Ginkgo biloba extracts inhibit spinal cord inflammation after secondary injury while simultaneously exerting neuroprotection after early decompression has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%